Citation performance of Malaysian scholarly journals in the Web of Science, 2006-2010 - Abrizah, Abdullah; Zainab, Awang Ngah; Edzan, N.N.; Koh, A.P. (Taylor & Francis, 2013)
There are several ways for the international scientific community to recognize the quality of a scholarly journal. Although controversial, the most widely used and reliable methodology. to identify the importance of a journal is through the citation it receives. This paper identifies the performance of scholarly journals published by Malaysian publishers in the Web of Science and reports the number of citations to Malaysian journals in terms of the cited and the citing journals. A search using the Thomson-Reuters citation database (Web of Science) was performed to identify highly cited Malaysian journals from 2006 to 2010. We identified 212 cited journals that received 9675 cited-papers, and a total of 9427 articles contributing to the 3184 journals citing Malaysian journals. More than fifty percent of all the articles that cited Malaysian journals were published in journals ranked in the first or second quartile by the journal Citation Report. Further analysis was done on the top 50 cited and citing journal titles. A steady growth of citations with a total increase of 56.9 was evident between the five year period examined. (C) 2013 Elsevier Inc. All rights reserved.